Hermeneutics and Phenomenology Problems When Applying Hermeneutic Phenomenological Method in Educational Qualitative Research - Kakkori, Leena (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2009)
Hermeneutic phenomenology is a research method used in qualitative research in the fields of education and other human sciences, for example nursing science. It is a widely used method example in Scandinavia, and Van Manen is well known for his hermeneutic phenomenological method. In many studies the hermeneutic phenomenological method is inarticulate or ambiguous. Researchers generally lack a common understanding of what this method actually is. One reason for that is that the expression “hermeneutic phenomenological method” is contradiction in terms. Hermeneutics and phenomenology have their own distinct history. Hermeneutics and phenomenology as philosophical disciplines have their own distinct aims and orientations. Hermeneutic is orientated to historical and relative meanings. Phenomenology in Husserlian sense is orientated to universal and absolute essences. Martin Heidegger connects hermeneutics and phenomenology in very sophisticated manner as hermeneutical phenomenology and he provides a very specific definition of his brand of phenomenology. For Heidegger, hermeneutical phenomenology is the research of the meaning of the Being as a fundamental ontology. However, this kind of phenomenology is of no use for educational qualitative research.